The Development of Matrimonial Property Law in Vietnam - Nguyên Thi My, Linh (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2018)
This article analyzes the development of the law on matrimonial property from ancient to modern times in Vietnam. It is clear that the development of the marriage law on property changes in each period of history. The article is not merely an analysis of marital property law in Vietnam but also a comparison with the laws of some countries such as China, France and Hungary. By reviewing and comparing, the article draws on legislative experiences on the regulations of the matrimonial property regime in Vietnam.